Determinants of Capital Structure: Evidence and Analysis of Developing (India) and Developed (USA) Nations. - Ahmed, Sarah Sameen (2020)
The Capital Structure of a firm, mainly constituting debt and equity, is referred to as the resources that firms turn to when investing or financing new projects, or for the daily operations of the firm. The literature around capital structure is extensive, with multiple studies defining and explaining the factors that influence financing decisions of firms, but most of these studies center around developed economies. Therefore, this study aims to examine the capital structure explanatory factors for a developing economy (India) and compare the results obtained to those of a developed economy (USA), in an effort to understand if there exist country specific factors that could influence capital structure decisions. For the regression model, data from 200 Indian companies and 200 US companies was taken, for a period of ten years (2010-2019). The study utilised three different dependent variables: long-term leverage, short-term leverage and total leverage, and seven independent variables namely, profitability, firm size, non-debt tax shield, growth opportunity, tangibility, liquidity and GDP growth rate. According to the results, the explanatory factors for both countries vary from the theoretical predictions, and the comparison revealed that the results were fairly dissimilar but not completely different to each other. The empirical evidence provided in this study does suggest that there exist some direct, indirect and generic country specific factors that influence capital structure decisions, which is the reason why results across countries of differing economic standing and growth are conflicting for each variable.